2017
DOI: 10.1021/acs.jpcc.7b05433
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes of Methacrylate-Based Monomers at the Air–Liquid Interface Due to Bulky Substituents

Abstract: Functionalization of monomers is important for various applications of polymers from electronics to surface coatings. Polymer chemists utilize methacrylate-based monomers to design polymers with wider application features. In this work, ethyl methacrylate-based monomers are functionalized with varying bulky substituents, methoxy (−OCH3), ethoxy (−OEt), isopropoxy (−O i Pr), tert-butoxy (−O t Bu), and phenoxy (−OPh), at the ethyl end position. These substituents are selected to understand the steric consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 102 publications
0
33
0
Order By: Relevance
“…And third, it was also found that ALGM1 presents an intramolecular hydrogen bond in its methacrylate unit (OH-O), displaying an in-between distance of 1.61 Å and an angle of 161.29 • , which correspond to a rather strong hydrogen bonding [44]. This intramolecular interaction makes the grafted M1 group rigid, imposing an additional impediment to ALGM1 chains to react with one another [45]. Taking the above-mentioned information into consideration, the computational results might provide an explanation for the observed trend in the mechanical properties: H-ALGM1 < H-ALGM2 < H-ALGM3 (p < 0.05).…”
Section: Density Functional Calculationsmentioning
confidence: 98%
“…And third, it was also found that ALGM1 presents an intramolecular hydrogen bond in its methacrylate unit (OH-O), displaying an in-between distance of 1.61 Å and an angle of 161.29 • , which correspond to a rather strong hydrogen bonding [44]. This intramolecular interaction makes the grafted M1 group rigid, imposing an additional impediment to ALGM1 chains to react with one another [45]. Taking the above-mentioned information into consideration, the computational results might provide an explanation for the observed trend in the mechanical properties: H-ALGM1 < H-ALGM2 < H-ALGM3 (p < 0.05).…”
Section: Density Functional Calculationsmentioning
confidence: 98%
“…The details on the SFG spectroscopic system are reported in our previous publications. [14][15][16][17] Briefly, the one-box ultrafast Ti:sapphire oscillator system from Spectra-Physics (Solstice) was utilized to generate 100 fs pulses at 795 nm with the power of $4 W before compression at a 1 kHz repetition rate. The 795 nm beam was then passed through a 50 : 50 beam splitter where the first half was directed towards a Fabry-Pérot Etalon (SLS Optics; spacing d ¼ 10.3 mm, free spectral range [FSR] ¼ 30.931 nm, effective finesse [F eff ] ¼ 71.30 at 800 nm), which converted the incoming beam into a time-asymmetric picosecond visible pulse with an $10-15 cm À1 full width half-maximum (FWHM).…”
Section: Broadband Sum Frequency Generationmentioning
confidence: 99%
“…On the other hand, the orientational analysis at the air-liquid interface was acquired by calculating the amplitude and intensity ratios between the CH 3 SS in SSP and SPS polarization combinations. 14,15 Spectral fitting was carried out using Eq. 1, which includes the background, non-resonance, and broadband IR pulse shape terms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations